Manga and anime in medical education: leontiasis ossea in ’Black Jack’ - Muscat, Michelle (k/a Mikhaila) (Research and Humanities in Medical Education, 2017)
’Black Jack’, the medical manga (Japanese comic/graphical novel) by the widely acclaimed godfather of manga, Ozamu Tezuka, follows the dramatized story of the unlicensed surgeon. It spans many manga volumes, and many episodes in the corresponding animated series (commonly referred to as anime), with a key focus on Black Jack’s superior, sensationalized, surgical abilities. This brief review focuses on the presence of a patient with leontiasis ossea at the beginning of the ’Black Jack 21’ anime series and highlights the use of media such as manga and anime in medical education.